A parametric decomposition of hotel-sector productivity growth - Chatzimichael, Konstantinos; Liasidou, Sotiroula (My University, 2019)
In this paper, we decompose hotel-sector total factor productivity growth into components attributable to changes in technical efficiency, scale effect, and technical change. The hotel-sector production Frontier is approximated parametrically using a primal approach requiring no data on output and input prices while permitting the conduction of statistical tests for the various features of the hotel-sector technology. Our empirical model relies on a flexible translog production function which allows to distinguish between Hicks-neutral and factor-biased technological progress. Using this framework, we estimate hotel-sector productivity growth and its components in a sample of 25 European countries from 2008 to 2015. Based on the empirical results, a cross-country comparison is performed and the sources of hotel-sector productivity are discussed. Finally, the implications of the study for hotel operators and policy makers are presented and a set of recommendations is developed for improving hotel sector productivity growth.
Keywords: Europe; Hotel-sector; Stochastic Frontier analysis; Technical efficiency; Total factor productivity growth; D24; D22; C33; M11